2018
DOI: 10.1002/dta.2408
|View full text |Cite
|
Sign up to set email alerts
|

L‐ and D‐threo ethylphenidate concentrations, pharmacokinetics, and pharmacodynamics in horses

Abstract: Ethylphenidate is a psychostimulant and analog of the commonly prescribed compound, methylphenidate (Ritalin®). There are a limited number of studies describing the disposition and pharmacologic/toxicological effects of ethylphenidate in any species. The abuse potential in equine athletes along with the limited data available regarding administration in horses necessitates further study. The objectives of the current study were to describe drug concentrations, develop an analytical method that could be used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Studies conducted in the 1960s clearly show that methylphenidate administration to horses at doses ranging from ≈0.1 to 1.2 mg/kg have effects on the central nervous system with increases in pulse, respiratory rate, and blood pressure observed [ 3 ]. The absorption, distribution, metabolism, and excretion properties of methylphenidate or structurally similar agents such as ethylphenidate have not been investigated in great detail in the horse, but some studies have shown that these compounds are relatively quickly cleared and primarily excreted in urine following intramuscular, intravenous, or oral administrations [ 3 , 4 , 5 ]. The major metabolite of methylphenidate in humans is ritalinic acid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted in the 1960s clearly show that methylphenidate administration to horses at doses ranging from ≈0.1 to 1.2 mg/kg have effects on the central nervous system with increases in pulse, respiratory rate, and blood pressure observed [ 3 ]. The absorption, distribution, metabolism, and excretion properties of methylphenidate or structurally similar agents such as ethylphenidate have not been investigated in great detail in the horse, but some studies have shown that these compounds are relatively quickly cleared and primarily excreted in urine following intramuscular, intravenous, or oral administrations [ 3 , 4 , 5 ]. The major metabolite of methylphenidate in humans is ritalinic acid.…”
Section: Introductionmentioning
confidence: 99%
“…The detection and confirmation of methylphenidate in urine and blood samples is challenging due to its rapid distribution and elimination half-lives, its metabolism to ritalinic acid, and the higher background of its major product ion (84 m / z ), which makes low-level detection challenging [ 3 , 4 , 5 ]. Analysis of hair samples offers an alternative sampling matrix that can extend the potential detection window following the administration of a prohibited substance [ 7 ].…”
Section: Introductionmentioning
confidence: 99%